Exploration of NIR Squaraine Contrast Agents Containing Various Heterocycles: Synthesis, Optical Properties and Applications - Shahir Sarasiya; Sara Sarasiya; Maged Henary (MDPI AG, 2023)
Squaraine dye is a popular class of contrast near-infrared (NIR) dyes. Squaraine dyes have shown the ability to be modified with various heterocycles. The indole moiety is the most notable heterocycle incorporated in squaraine dyes. A tremendous amount of work has gone into developing indole-based squaraine dyes and determining their applications. The optical properties of squaraine dyes containing an indole moiety facilitate high quantum yields and molar absorptivity, but the absorbance maxima is capped near 700 nm. This is the major limitation of indole-based squaraine dyes. In comparison, other heterocycles with larger conjugated systems such as quinoline and perimidine have demonstrated promising optical properties and immense potential for modifications, albeit with limited development. Quinoline- and perimidine-based squaraine dyes have molar extinction coefficients over 100,000 M−1 cm−1 and absorbances over 800 nm. This report will look at indole-, quinoline-, and perimidine-based squaraine dyes. Due to the sheer number of reported dyes, the search for indole-based squaraine dyes has been limited to reports from the past five years (2018-2023). For quinoline- and perimidine-based squaraine dyes, a holistic search was performed to analyze the optical properties and applications, due to the abovementioned limitation. This report will evaluate the three different classes of squaraines: indole-, quinoline-, and perimidine-based, to evaluate their optical properties and applications, with the goal of encouraging the exploration of other heterocycles for use in squaraine dyes.